2006
DOI: 10.1248/bpb.29.302
|View full text |Cite
|
Sign up to set email alerts
|

Glycosidase Inhibitory Flavonoids from Sophora flavescens

Abstract: The methanol extract of Sophora flavescens showed a potent glycosidase inhibitory activity. Active components were identified as well-known flavonoid antioxidants: kushenol A (1), (؊)-kurarinone (2), sophoraflavanone G (3), 2-methoxykurarinone (4), kurarinol (5), 8-prenylkaempferol (6), isoxanthohumol (7), kuraridin (8) and maackian (9). All flavonoids were effective inhibitors of a a -glucosidase and b b -amylase. Interestingly, lavandulylated flavanones 1-5 had strong a a -glucosidase inhibitory activities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 28 publications
2
69
0
2
Order By: Relevance
“…Kurarinol is reported to be a prenylated flavanone and an effective inhibitor of alpha-glucosidase, beta-amylase, and cGMP phosphodiesterase-5, and also inhibits diacylglycerol acyltransferase activity. 13,19,21,22) On the other hand, kuraridinol is a chalcone compound belonging to the prenylated flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…Kurarinol is reported to be a prenylated flavanone and an effective inhibitor of alpha-glucosidase, beta-amylase, and cGMP phosphodiesterase-5, and also inhibits diacylglycerol acyltransferase activity. 13,19,21,22) On the other hand, kuraridinol is a chalcone compound belonging to the prenylated flavonoids.…”
Section: Resultsmentioning
confidence: 99%
“…8) Biological investigations have mainly focused on its antibacterial, cytotoxic, tyrosinase inhibitory, and glycosidase inhibitory properties. [9][10][11][12] Although the antioxidant benefits of flavonoids from S. flavescens have been reported in a few cases, 13,14) there is no report as to whether the compounds inhibit LDL oxidation and thus their utility toward atherosclerosis treatment is currently not known.…”
mentioning
confidence: 99%
“…It is to be mentioned here that salacinol and kotalanol showed a fully competitive type of inhibition on each α-glucosidase 30 , while acarbose showed a full competitive inhibition towards intestinal sucrase 31 and maltase 13 but noncompetitive type of inhibition towards pancreatic amylase 32 . Flavonoids isolated from the roots of Sophora flavescens showed a noncompetitive type of inhibition for α-glucosidases 33 . It was reported that natural circuminoid (bisdemethoxycurcumin) inhibited α-glucosidase in a noncompetitive fashion 34 .…”
Section: Discussionmentioning
confidence: 99%